1999
DOI: 10.1038/sj.ejcn.1600869
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the salt restriction diet among people with mildly elevated blood pressure

Abstract: Objective: The aim of the study was to examine the adherence to a salt restriction diet and the effect of salt restriction on blood pressure in free living subjects with mildly elevated blood pressure. Design: Subjects with mildly elevated blood pressure participated in a controlled study on the effect of salt restriction on blood pressure. Subjects received oral and written instructions by a clinical nutritionist to reduce sodium chloride intake to ®ve grams per day. A low sodium bread (0.5%) was supplied fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 26 publications
0
43
0
3
Order By: Relevance
“…Another study showed that selfmonitoring of urinary salt excretion at home, using chloride titrator strips, could, in conjunction with dietary counseling, facilitate compliance with a reduced salt intake (19). However, another report indicated that short counseling sessions with advice on salt restriction were not successful in producing dietary changes (5). Taken together, these results suggest that repeated monitoring of urinary salt excretion, along with providing feedback to patients, is the most important and practical way to achieve the reduction of salt intake in individual hypertensives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that selfmonitoring of urinary salt excretion at home, using chloride titrator strips, could, in conjunction with dietary counseling, facilitate compliance with a reduced salt intake (19). However, another report indicated that short counseling sessions with advice on salt restriction were not successful in producing dietary changes (5). Taken together, these results suggest that repeated monitoring of urinary salt excretion, along with providing feedback to patients, is the most important and practical way to achieve the reduction of salt intake in individual hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…Salt restriction is now also widely promoted as an effective non-pharmacological approach to managing mild hypertension, as well as an important adjunct to pharmacological treatment in moderate and severe hypertension (3)(4)(5)(6)(7). The seventh report of the Joint National Committee (JNC 7) recommends sodium reduction to a level of no more than 100 mmol/day in hypertensive patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to reduced sodium regimens has generally been low. Simple advice provided at health care settings, even when given at every visit, tends to have low effectiveness (4)(5)(6)(7). With intensive counseling, only 20% to 40% of participants in sodium reduction trials reduce their sodium intakes to below the recommended upper limit of 2,300 mg/day (100 mmol/day) (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The findings of the present study are consistent with these reports. However, more vigorous intervention, including group meetings and a free supply of low-salt bread, did reduce salt excretion (11,12). Although single-session dietary counseling by dieticians in addition to simple counseling by attending physicians may seem to be unproductive efforts, particularly in patients who consume large amounts of salt despite repeated instructions by their attending physicians (Fig.…”
Section: Discussionmentioning
confidence: 99%